1966 - Fung, Ronald Y. K.; (1937-...) (Hong Kong, 1966)
This magazine presents these articles: Proving God's existence, delivered from death, is christ risen indeed? The immutable freedom, God beckons, editorial: divorce, notes & news, have you read? Untouchable, daniel, a year in Nazareth, effective evangelism.
Keywords: The way